من أسرار التعريف والتنكير في سورة آل عمران: دراسة تحليلية - أشمر، بسام عماد; الشرقاوي، محمد شحاتة عبدالحميد (جامعة المدينة العالمية - كلية اللغات, 2020)
جاء هذا البحث مساعداً ومسهماً في فهم قسم من أقسام علم النحو العربي، وهو مبحث التعريف والتنكير، مفصلا القول في ذكر مفهوم التعريف والتنكير في اللغة العربية، مع الإتيان على أنواعهما وأحكامهما ودواعيهما، من خلال دراسة أقوال النحويين والبلاغيين في هذا الموضوع. وقد وضح البحث بداية المراد بمصطلحي المعرفة والنكرة، ثم ذكر أقسام كل منهما، وبين اختلاف علماء النحو في عدد المعارف، واختلافهم في بيان ترتيب المعارف حسب قوة تعريفها، إلى غير ذلك من الأغراض النحوية. كما سلط البحث الضوء كذلك على دواعي التنكير والتعريف، مفصلاً القول في كل نوع من أنواع المعارف، مظهراً المواطن التي يحسن بها التنكير والإبهام، والمواطن التي يحسن بها التعريف والإيضاح، وذلك بالبحث عنها وتحليلها في سورة آل عمران. ووفقا لهذه الأهداف المرجوة، ورغبة وسعياً في الوصول إلى إجابات شافية لأسئلة البحث، فقد اعتمد في هذا البحث المنهج الوصفي، والمنهج التحليلي، فالوصفي للوقوف على معاني المصطلحات الرئيسية وذكر معانيها ودلالاتها، والتحليلي لتحليل النصوص المراد دراستها في هذا المبحث.
This research is to assist in and contribute to understanding a topic of the Arabic grammar; definiteness and indefiniteness. It mentions in detail the concept of definiteness and indefiniteness in the Arabic language, stopping at their types, rules, and causes, through studying the sayings of grammarians and rhetoricians on this subject.The research starts by explaining the meaning of definiteness and indefiniteness, then mentions the types of each of them and demonstrates the different opinions of grammarians in the number of definite nouns and their categorization according to the strength of their definiteness, in addition to other grammar purposes. The research also highlights the causes for definiteness and indefiniteness, detailing each of the definiteness types and showing the instances where indefiniteness and ambiguity are preferable, while giving examples to demonstrate this from the Holy Quran, noble Prophetic Hadith, Arabic poetry, and what was circulated on the tongues of Arabs. The research then tries to do its best in detailing these arguments between grammarians and rhetoricians, explaining the meanings derived from such arguments by searching for and analyzing them in the Surahs of Ale Emran accordance with these intended objectives, and with the desire and effort to find satisfactory answers to the questions of the research, the descriptive method and the analytic method were adopted throughout this research; the descriptive method is to examine the meanings of the key terms and their semantics, while the analytic method is to analyze the texts and prove the strong relationship that connects the topics of linguistics with literature and rhetoric.
Keywords: القرآن الكريم -- التفاسير اللغوية -- النحو العربي -- إعراب القرآن -- السور والآيات